2019
DOI: 10.1002/ajh.25390
|View full text |Cite
|
Sign up to set email alerts
|

Hyperfiltration during early childhood precedes albuminuria in pediatric sickle cell nephropathy

Abstract: Background In patients with diabetes mellitus, hyperfiltration precedes the development of albuminuria. Pediatric sickle cell anemia (SCA) patients have a high prevalence of hyperfiltration and albuminuria during early childhood and adolescence. We tested the hypothesis that hyperfiltration precedes the development of albuminuria in a longitudinal pediatric SCA cohort. Methods We identified 91 participants with HbSS or SB0 thalassemia 5‐21 years of age enrolled in a longitudinal sickle cell nephropathy cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 41 publications
2
66
0
1
Order By: Relevance
“…Only persistent, and not transient, albuminuria has been linked to kidney diseases in children and adults without SCA. [19][20][21] Previous longitudinal studies of sickle nephropathy showed that albuminuria measurements are variable 22,23,25 ; almost one-third of patients with albuminuria had intermittent albuminuria over years in 1 study, whereas only 9% of patients developed PA in another study. 37,38 In our study, albuminuria was common overall; however, PA, and not merely the presence of albuminuria, was associated with a decline in eGFR and development of CKD in adults.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Only persistent, and not transient, albuminuria has been linked to kidney diseases in children and adults without SCA. [19][20][21] Previous longitudinal studies of sickle nephropathy showed that albuminuria measurements are variable 22,23,25 ; almost one-third of patients with albuminuria had intermittent albuminuria over years in 1 study, whereas only 9% of patients developed PA in another study. 37,38 In our study, albuminuria was common overall; however, PA, and not merely the presence of albuminuria, was associated with a decline in eGFR and development of CKD in adults.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, Lebensburger et al 25 showed that in children with SCA, PA was associated with hyperfiltration. Although we did not find an association between hyperfiltration and PA, likely because of the broad age range in our study, we found that PA may be a marker of CKD in SCA, because it correlates with a rapid decline in eGFR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nearly all SCA patients are affected by sickle cell nephropathy (SCN), and 16-18% of mortality is attributed to the manifestations of SCN [1][2][3]. SCN is detectable early in the majority of infants with SCA as glomerular hyperfiltration, an important early mediator of chronic glomerular damage [4][5][6]. This is followed by an increasing prevalence (26-46%) of abnormal albuminuria in the teenage and young adult years [2,7].…”
Section: Introductionmentioning
confidence: 99%